Destination Image Perception Mediated by Experience Quality : The Case of Qingzhou as an Emerging Destination in China - Guan, Li Ping; Norazirah, Ayob; Puah, Chin Hong; Mohammad Affendy, Arip; Jong, Meng Chang (MDPI, 2023)
: In recent years, the competition in the tourism market has become more and more fierce. Tourism destinations need to ensure they have sufficient sources of tourists, and thus, improving their market competitiveness, image, and reputation are particularly important. For this reason, tourism academia has always attached great importance to the study of tourism destination image. Many studies have shown that tourists’ travel behavior is largely influenced by their perception of tourism destinations. Research on heritage tourism from the supply perspective is relatively abundant, whereas not much research has been conducted on the demand side, and the influence of heritage tourism on the perception of a destination’s image has rarely been discussed. This study examines destination image perceptions through three components: cognition, affection, and quality of experience. We propose a conceptual model that clarifies how the quality of experience mediates the formation of cognition and affection with regard to emerging destinations in mainland China. This study employed the PLS-SEM discontinuous two-stage approach, which involved the examination of higher-order constructs (HOCs). The results from a sample of 475 visitors to the ancient city of Qingzhou in mainland China showed that cognition positively influences affection, and they both positively influence the overall image. Quality of experience was shown to be a mediating factor between cognition and affection. Moreover, the variables under quality of experience were confirmed to be consistent with those under cognition.